Composite lithium iron manganese phosphate positive electrode material and preparation method thereof
Through the hydrothermal reaction method, the preparation process of lithium manganese iron phosphate positive electrode material is simplified, and the problems of uneven particle size distribution and complex process in the existing methods are solved, thereby achieving efficient and low-cost material preparation.
Patent Information
- Application Number
- CN202411937093.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-26
- Publication Date
- 2025-04-01
AI Technical Summary
In the existing preparation methods of lithium manganese iron phosphate positive electrode materials, the high-temperature solid phase method leads to uneven particle size distribution, while the liquid phase method requires a secondary calcination process and a complicated process.
The composite lithium manganese iron phosphate positive electrode material was prepared by hydrothermal method, and micro-sized grains of uniform size were formed through two hydrothermal reactions, avoiding the calcination step and simplifying the process.
The preparation of lithium manganese iron phosphate cathode material with large particle size and good electrochemical performance is achieved, without additional calcining steps, improving production efficiency, reducing costs, and ensuring high quality of the material.
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of lithium manganese iron phosphate materials, and in particular relates to a composite lithium manganese iron phosphate positive electrode material and a preparation method thereof. Background Art
[0002] The preparation method of lithium manganese iron phosphate positive electrode materials has a significant impact on their particle size distribution and electrochemical performance. The lithium manganese iron phosphate positive electrode materials prepared by the high-temperature solid-phase method often have uneven particle size distribution, while the materials prepared by the liquid-phase method usually have nano-scale particle size and stable quality control. Among them, the lithium manganese iron phosphate material prepared by the hydrothermal method has a nano-scale particle size and insufficient crystallinity, so subsequent calcination treatment is usually required to improve its performance. During the calcination and post-processing process, the gas environment, heating rate, calcination temperature and other grinding and processing processes need to be strictly controlled to stably control the particle size and optimize the material performance.
[0003] To obtain high-quality lithium iron manganese phosphate cathode materials, the liquid phase method is widely used because it can produce materials with uniform particle size and good electrochemical properties. However, the present invention adopts a hydrothermal method to prepare lithium iron manganese phosphate cathode materials, avoiding the secondary calcination process commonly used in the liquid phase method, thereby simplifying the preparation process. By precisely controlling the conditions of the hydrothermal synthesis, the present invention produces lithium iron manganese phosphate cathode materials with large particle size and good electrochemical properties without the need for an additional calcination step. This method not only improves production efficiency and reduces costs, but also ensures the high quality of the material. Summary of the Invention
[0004] To address the above-mentioned technical problems, the present invention provides a composite lithium iron manganese phosphate cathode material and a method for preparing the same. The method utilizes a hydrothermal method to prepare the composite lithium iron manganese phosphate cathode material without requiring a calcination step. The composite lithium iron manganese phosphate cathode material prepared by the present invention has a high tap density and exhibits excellent discharge performance and good cycling stability.
[0005] The present invention solves the above technical problems through the following technical solutions.
[0006] A method for preparing a composite lithium manganese iron phosphate positive electrode material comprises the following steps:
[0007] The precursor solution is subjected to a hydrothermal reaction, zinc MOF and sodium poly(p-styrene sulfonate) (CAS No.: 25704-18-1, Mw: 80,000) are added, and a secondary hydrothermal reaction is performed to obtain a composite manganese iron phosphate lithium cathode material;
[0008] The zinc MOF is ZIF-70 (CAS No.: 1207355-49-4) or ZIF-8 (CAS No.: 59061-53-9).
[0009] In some preferred embodiments, the precursor solution includes a lithium source solution, a manganese source solution, an iron source solution, and a phosphorus source solution.
[0010] In some preferred embodiments, the lithium source is lithium hydroxide, lithium carbonate, lithium dihydrogen phosphate or lithium sulfate, preferably lithium hydroxide.
[0011] In some preferred embodiments, the manganese source is manganese sulfate, manganese chloride or manganese carbonate, preferably manganese sulfate.
[0012] In some preferred embodiments, the iron source is ferrous sulfate.
[0013] In some preferred embodiments, the phosphorus source is phosphoric acid.
[0014] In some preferred embodiments, the precursor solution is prepared by sequentially adding a phosphorus source solution, a manganese source solution, and an iron source solution to a lithium source solution.
[0015] In some preferred embodiments, the molar ratio of Li:Mn:Fe:P in the precursor solution is 1:x:1-x:1, where x=0.3-0.7.
[0016] In some preferred embodiments, ascorbic acid in an amount equivalent to ferrous sulfate needs to be added to the precursor solution.
[0017] In some preferred embodiments, 10-30% of the total volume of polyethylene glycol is further added to the precursor solution.
[0018] In some preferred embodiments, the temperature of the hydrothermal reaction is 170-200°C, preferably 180-190°C.
[0019] In some preferred embodiments, the hydrothermal reaction time is 5 to 8 hours, preferably 5 to 6 hours.
[0020] In some preferred embodiments, the temperature of the secondary hydrothermal reaction is 150-170°C, preferably 150-160°C.
[0021] In some preferred embodiments, the secondary hydrothermal reaction time is 2 to 5 hours, preferably 3 to 4 hours.
[0022] In some preferred embodiments, the preparation process includes two hydrothermal reactions. The first hydrothermal reaction is intended to achieve the initial formation of the lithium manganese iron phosphate raw material, while the second hydrothermal reaction is intended to promote the growth of lithium manganese iron phosphate grains after the addition of zinc MOF. Therefore, if the lithium manganese iron phosphate overreacts in the initial hydrothermal reaction, the overall particle size of the positive electrode material will be too small.
[0023] In some preferred embodiments, the pore volume of the zinc MOF is 0.6 to 0.75 cm3 / g.
[0024] In some preferred embodiments, the BET specific surface area of the zinc MOF is 1300-1600 m 2 / g.
[0025] In some preferred embodiments, the zinc MOF has a D50 of 1 to 5 μm.
[0026] In some preferred embodiments, zinc MOF has a large specific surface area and a certain pore volume, which can promote the grain growth of lithium manganese iron phosphate; MOF materials with zinc as the metal center are beneficial to the conductive properties of the positive electrode material.
[0027] In some preferred embodiments, the Mw of the sodium poly(p-styrene sulfonate) is 70,000 to 80,000.
[0028] In some preferred embodiments, sodium poly(p-styrene sulfonate) as an amphoteric polymer copolymer can improve the compatibility between zinc MOF and lithium manganese iron phosphate.
[0029] In some preferred embodiments, the mass ratio of the lithium source in the precursor to the zinc MOF is 100:8-20, preferably 100:8-15.
[0030] In some preferred embodiments, the mass ratio of the zinc MOF to the sodium poly(p-styrene sulfonate) is 10:1 to 5, preferably 10:2 to 4.5.
[0031] In some preferred embodiments, post-treatment is required after the secondary hydrothermal reaction;
[0032] The post-treatment includes the steps of filtering, washing and drying;
[0033] Furthermore, the drying is vacuum drying, and the drying temperature is 100-130°C.
[0034] The composite lithium iron manganese phosphate positive electrode material is prepared by the aforementioned preparation method of the composite lithium iron manganese phosphate positive electrode material.
[0035] In some preferred embodiments, the tap density of the composite manganese iron phosphate lithium positive electrode material is 0.8 to 1.2 g / cm 3 .
[0036] On the basis of conforming to the common sense in this field, the above-mentioned preferred conditions can be arbitrarily combined to obtain the preferred embodiments of the present invention.
[0037] Compared with the prior art, the present invention has the following beneficial effects:
[0038] 1. The present invention relates to a method for preparing a composite lithium iron manganese phosphate cathode material, which is achieved through two hydrothermal reactions. First, a first hydrothermal reaction initially forms microscopic lithium iron manganese phosphate particles. Subsequently, zinc metal phosphate (MOF) is added to the resulting product, and a second hydrothermal reaction promotes grain growth. Furthermore, the addition of sodium poly(p-styrene sulfonate) improves the compatibility between zinc metal phosphate (MOF) and lithium iron phosphate, thereby producing a uniformly sized micron-sized composite lithium iron manganese phosphate cathode material.
[0039] 2. The tap density of the composite manganese iron phosphate lithium positive electrode material of the present invention is 0.8 to 1.2 g / cm 3 The capacity retention rate (25°C) of the battery was tested at 96-99% for 100 cycles at a rate of 1.0C in the voltage range of 2.0-4.3V. DETAILED DESCRIPTION
[0040] To facilitate understanding of the present invention, the present invention will be described more comprehensively and meticulously below in conjunction with preferred embodiments, but the protection scope of the present invention is not limited to the following specific embodiments.
[0041] Unless otherwise defined, all technical terms used hereinafter have the same meanings as those generally understood by those skilled in the art. The technical terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention.
[0042] The "ranges" disclosed herein are defined in terms of lower and upper limits. A given range is defined by selecting a lower limit and an upper limit, and the selected lower and upper limits define the boundaries of the particular range. Ranges defined in this manner can be inclusive or exclusive of the end values and can be combined in any manner, i.e., any lower limit can be combined with any upper limit to form a range. For example, if ranges of 60-120 and 80-110 are listed for a particular parameter, it is understood that ranges of 60-110 and 80-120 are also contemplated. Furthermore, if the minimum range values listed are 1 and 2, and if the maximum range values listed are 3, 4, and 5, then the following ranges are all contemplated: 1-3, 1-4, 1-5, 2-3, 2-4, and 2-5. In this disclosure, unless otherwise indicated, the numerical range "ab" is an abbreviation for any combination of real numbers between a and b, where a and b are both real numbers. For example, the numerical range "0-5" indicates that all real numbers between "0-5" have been listed herein, and "0-5" is merely an abbreviation for these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0043] Unless otherwise specified, all embodiments and optional embodiments of the present invention can be combined with each other to form new technical solutions.
[0044] Unless otherwise specified, all technical features and optional technical features of the present invention can be combined with each other to form a new technical solution.
[0045] Unless otherwise specified, all steps of the present invention may be performed sequentially or randomly, preferably sequentially. For example, "the method includes steps (a) and (b)" indicates that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, "the method may further include step (c)" indicates that step (c) may be added to the method in any order, for example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.
[0046] Unless otherwise specified, the terms "include" and "comprising" used in the present invention may be open-ended or closed-ended. For example, "include" and "comprising" may mean that other components not listed may also be included or that only the listed components are included.
[0047] Unless otherwise specified, the term "or" is inclusive in this disclosure. For example, the phrase "A or B" means "A, B, or both A and B." More specifically, the condition "A or B" is satisfied by any of the following conditions: A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).
[0048] The raw materials used in the following examples and comparative examples are:
[0049] ZIF-70 was purchased from Shanghai Kaishu Chemical Technology Co., Ltd. and has a pore volume of 0.7 cm 3 / g, BET ratio 1300~1500m 2 / g, D50=3-5 μm; its ligands are imidazole (CAS: 288-32-4) and 2-nitroimidazole (CAS: 527-73-1).
[0050] ZIF-8 was purchased from Shanghai Kaishu Chemical Technology Co., Ltd. and has a pore volume of 0.66 cm 3 / g, BET specific surface area 1500m 2 / g, D50=1 μm; its ligand is 2-methylimidazole (CAS: 693-98-1).
[0051] Sodium polystyrene sulfonate (CAS No.: 25704-18-1, Mw: 80,000) was purchased from Hubei Bojie Biotechnology Co., Ltd.
[0052]
Preparation method of composite lithium manganese iron phosphate positive electrode material
[0053] Example 1
[0054] 1. Prepare the precursor solution: Add 8 V / V% concentrated phosphoric acid solution to 1M lithium hydroxide solution, then add 0.5M ferrous sulfate solution and 0.5M manganese sulfate solution. The precursor solution also contains an equal molar amount of ascorbic acid with ferrous phosphate. Finally, add 20% of the total volume of PEG400 to the precursor solution. The resulting precursor solution has a molar ratio of Li:Mn:Fe:P of 1:0.5:0.5:1.
[0055] 2. Heat the precursor solution to 180°C in a hydrothermal reactor for 6 hours. After cooling, add zinc MOF and sodium poly(p-styrene sulfonate) and heat to 150°C for 4 hours.
[0056] Among them, the mass ratio of lithium hydroxide and zinc MOF is 100:15, and the mass ratio of zinc MOF: sodium poly(p-styrene sulfonate) is 10:4.5.
[0057] After the reaction is completed, the mixture is cooled, filtered, washed with water, and then vacuum dried at 120° C. for 24 hours to obtain a composite manganese iron phosphate lithium positive electrode material.
[0058] Example 2
[0059] The difference between this embodiment and embodiment 1 is that:
[0060] The mass ratio of lithium hydroxide to zinc MOF is 100:8.
[0061] Example 3
[0062] The difference between this embodiment and embodiment 1 is that:
[0063] The mass ratio of zinc MOF: sodium poly(p-styrene sulfonate) is 10:2.5.
[0064] Example 4
[0065] The difference between this embodiment and embodiment 1 is that:
[0066] The hydrothermal reaction temperature is 190°C and the time is 5 h.
[0067] Example 5
[0068] The difference between this embodiment and embodiment 1 is that:
[0069] The temperature of the secondary reaction is 160°C and the time is 3 hours.
[0070] Comparative Example 1
[0071] The difference between this comparative example and Example 1 is:
[0072] In this comparative example, no sodium poly(p-styrene sulfonate) was added.
[0073] Comparative Example 2
[0074] The difference between this comparative example and Example 1 is:
[0075] The temperature of the hydrothermal reaction was 180°C and the time was 10 h.
[0076]
Composite lithium manganese iron phosphate positive electrode material
[0077] The invention relates to a composite manganese iron phosphate lithium positive electrode material prepared by a preparation method of the composite manganese iron phosphate lithium positive electrode material.
[0078]
Positive electrode
[0079] A positive electrode plate includes the composite lithium iron manganese phosphate positive electrode material of the embodiment of the present invention or the composite lithium iron manganese phosphate positive electrode material prepared by the preparation method of the embodiment of the present invention.
[0080] In some embodiments, the positive electrode sheet includes a current collector and a positive electrode film layer disposed on at least one surface of the current collector;
[0081] The positive electrode film layer contains the composite lithium iron manganese phosphate positive electrode material of the embodiment of the present invention or the composite lithium iron manganese phosphate positive electrode material prepared by the preparation method of the embodiment of the present invention.
[0082] In the above-mentioned “at least one surface of the current collector”, the surface refers to the surface of the current collector perpendicular to the thickness direction of the current collector.
[0083] Exemplarily, the thickness of the positive electrode plate is 0.15 to 10 mm; this thickness is only exemplary, and the thickness can be adjusted according to actual needs and is not limited to this thickness range.
[0084] In some embodiments, the current collector material includes one or more of a carbon material, a metal material, and a carbon fiber composite material.
[0085] In some embodiments, the carbon material includes one or more of natural graphite, artificial graphite, carbon black, and carbon fiber.
[0086] In some embodiments, the metal material includes one or more of aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver, silver alloy, copper, and copper alloy.
[0087] In some embodiments, the positive electrode film layer contains the composite lithium iron manganese phosphate positive electrode material of the embodiment of the present invention or the composite lithium iron manganese phosphate positive electrode material prepared by the preparation method of the embodiment of the present invention; it may also contain at least one of a conductive agent, a dispersant, and a binder.
[0088] In some embodiments, the mass ratio of the composite manganese iron phosphate lithium cathode material, the conductive agent, the dispersant, and the binder is not limited to a specific ratio and can be selected according to actual needs. For example, the mass ratio can be (60-200): (2-15): (1-15): (1-15), wherein the mass ratio can be a typical but non-limiting mass ratio such as 80:10:10:10 or a range between any two mass ratios. This example is only an example, and the actual ratio is not limited by this mass ratio.
[0089] In some embodiments, the method for preparing a positive electrode film generally includes:
[0090] The composite lithium manganese iron phosphate positive electrode material, which may include at least one of a conductive agent, a dispersant, and a binder, is dispersed in a solvent and stirred to form a positive electrode slurry;
[0091] The positive electrode slurry is coated on the current collector, and the positive electrode film layer is obtained through the steps of drying and cold pressing.
[0092] In some embodiments, the solvent includes N-methylpyrrolidone (NMP), but is not limited thereto.
[0093] In some embodiments, the types and contents of the conductive agent, dispersant, and binder are not specifically limited and can be selected according to actual needs.
[0094] Exemplarily, the conductive agent includes one or more of carbon black and graphite. Carbon black includes one or more of acetylene black, carbon fiber, oxidized carbon nanotubes, and Ketjen black. Graphite includes one or more of natural graphite, artificial graphite, fullerene (C60), and graphene.
[0095] Exemplary dispersants include polyvinyl pyrrolidone (PVP), polyacrylic acid (PAA), polymethacrylic acid (PMA), polyphosphate (PAE), hexamethyldiaminetetramethylenephosphonic acid (HMDTMP), polyvinyl alcohol (PVA), sodium dodecylbenzenesulfonate (LAS), polyethylene glycol (PEG), and isopropanolamine. These dispersants have good dispersing effects under acidic conditions.
[0096] For example, the binder may include one or more of polyvinylidene fluoride (PVDF), polyacrylate glue, sodium carboxymethyl cellulose (CMC), polytetrafluoroethylene (PTFE), polyvinyl alcohol (PVA), and polyacrylic acid (PAA).
[0097] In some embodiments, the positive electrode film layer may further include a thickener. For example, the thickener may include one or more of hydroxypropyl methylcellulose (HPMC), polyvinyl alcohol (PVA), and sodium carboxymethylcellulose (CMC).
[0098] Exemplarily, the thickness of the positive electrode film layer is 0.1 mm to 8 mm; this thickness is only exemplary, and the thickness can be adjusted according to actual needs and is not limited to this thickness range.
[0099]
Battery
[0100] A battery comprising a positive electrode sheet, a separator, a negative electrode sheet and an electrolyte;
[0101] The positive electrode plate includes the positive electrode plate of the embodiment of the present invention.
[0102] The battery of the embodiment of the present invention has excellent conductivity, cycle stability and rate performance because the positive electrode adopts a positive electrode plate comprising the composite lithium iron manganese phosphate positive electrode material of the embodiment of the present invention or the composite lithium iron manganese phosphate positive electrode material prepared by the preparation method of the embodiment of the present invention, thereby making the battery positive electrode have excellent conductivity, cycle stability and rate performance.
[0103] In some embodiments, the separator includes one or more of a porous polymer membrane, a non-woven fabric separator, and an inorganic composite membrane.
[0104] In some embodiments, the material of the porous polymer membrane includes polyethylene (PE) and / or polypropylene (PP).
[0105] In some embodiments, the material of the non-woven fabric separator includes one or more of polyimide (PI), polyester (such as polyethylene terephthalate PET), cellulose, polyamide (PA), and aramid.
[0106] In some embodiments, the non-woven membrane is a nanofiber non-woven membrane, including a polyimide nanofiber membrane. In this case, the nanofiber non-woven membrane has a higher specific surface area and stronger adsorption capacity, which can more effectively isolate the positive and negative electrodes and promote the transmission of lithium ions.
[0107] In some embodiments, the non-woven membrane is a ceramic-coated non-woven membrane, i.e., a ceramic powder (such as Al2O3, SiO2, etc.) is coated on the surface of the non-woven membrane (with a thickness of 2 μm to 15 μm). This ceramic-coated non-woven membrane not only inherits the high porosity and air permeability of the non-woven fabric, but also increases its thermal stability and mechanical strength.
[0108] In some embodiments, the inorganic composite membrane includes a ceramic-coated composite membrane and an inorganic-organic composite membrane;
[0109] Among them, ceramic-coated composite membranes are polymer membranes (such as polyethylene PE, polypropylene PP, etc.) coated with one or more layers of ceramic coating; the ceramic coating can significantly improve the thermal and chemical stability of the membrane while maintaining the flexibility and mechanical strength of the polymer membrane;
[0110] Inorganic-organic composite membranes are made by combining inorganic materials with polymer materials through blending, copolymerization or lamination. This composite membrane combines the advantages of inorganic and polymer materials and has higher comprehensive performance.
[0111] In some embodiments, the isolation film has a thickness of 60-100 μm.
[0112] In some embodiments, the negative electrode sheet is a common battery electrode sheet, generally comprising a current collector and a negative electrode film layer. The negative electrode film layer contains a negative electrode active material. The specific negative electrode material and content can be selected based on actual needs and are not limited. The preparation of the negative electrode film layer is essentially the same as that of the positive electrode film layer.
[0113] In some embodiments, the electrolyte includes an electrolyte salt and a solvent. The materials and contents of the electrolyte salt and the solvent are selected according to actual needs and are not limited.
[0114]
application
[0115] Application of the composite lithium iron manganese phosphate positive electrode material of the embodiment of the present invention, the composite lithium iron manganese phosphate positive electrode material prepared by the preparation method of the composite lithium iron manganese phosphate positive electrode material of the embodiment of the present invention, the positive electrode plate of the embodiment of the present invention or the battery of the embodiment of the present invention in household appliances, electric vehicles, electric vehicles, electric trains, ships, satellites or energy storage systems.
[0116] Test Example
[0117] The composite lithium manganese iron phosphate cathode materials prepared in the above examples and comparative examples were prepared into button-type half-cells, and the preparation steps were as follows:
[0118] (1) Preparation of positive electrode slurry: The composite manganese iron phosphate lithium positive electrode material: carbon nanotubes: polyvinylidene fluoride were mixed in a mass ratio of 80:10:10, and solvent N-methylpyrrolidone (NMP) was added to adjust the viscosity to 4000-8000 mPa·s to prepare a positive electrode slurry.
[0119] (2) The positive electrode slurry is evenly coated on one surface (perpendicular to the thickness direction) of the aluminum foil (positive electrode current collector) and dried, and then rolled and sheared to obtain a positive electrode sheet containing a positive electrode film layer.
[0120] (3) Using lithium hexafluorophosphate-ethyl methyl carbonate as the electrolyte and polypropylene as the isolation membrane, the prepared positive electrode sheet and negative lithium sheet are combined to make a button half-cell.
[0121] The button half-cell was tested using a blue-power device for 100 cycles at a 1.0C rate in the voltage range of 2.0-4.3V to determine its capacity retention (25°C). The test results are shown in Table 1 below.
[0122] Table 1
[0123] - <![CDATA[Tap density (g / cm 3 )]]> Capacity retention rate (%) Example 1 1.13 98.7 Example 2 0.84 97.6 Example 3 0.93 96.5 Example 4 1.16 97.8 Example 5 1.07 96.4 Comparative Example 1 0.72 86.2 Comparative Example 2 0.66 81.5
[0124] Unless otherwise specified, all raw materials, reagents, instruments, and equipment used in the present invention can be purchased from the market or prepared by existing methods. The specific embodiments described above further illustrate the purpose, technical solutions, and beneficial effects of the present invention. It should be understood that the above description is only a specific embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention shall be included in the scope of protection of the present invention.
Claims
1. A method for preparing a composite lithium manganese iron phosphate positive electrode material, characterized in that: The following steps are involved: The precursor solution is subjected to a hydrothermal reaction, and zinc MOF and sodium poly(p-styrene sulfonate) are added to perform a secondary hydrothermal reaction to obtain a composite manganese iron phosphate lithium cathode material; The zinc MOF is ZIF-70 or ZIF-8.
2. The method for preparing the composite lithium iron manganese phosphate positive electrode material according to claim 1, characterized in that: The precursor solution includes a lithium source solution, a manganese source solution, an iron source solution and a phosphorus source solution; The lithium source is lithium hydroxide, lithium carbonate, lithium dihydrogen phosphate or lithium sulfate; The manganese source is manganese sulfate, manganese chloride or manganese carbonate; The iron source is ferrous sulfate; The phosphorus source is phosphoric acid.
3. The method for preparing the composite lithium iron manganese phosphate positive electrode material according to claim 1, characterized in that: The molar ratio of Li:Mn:Fe:P in the precursor solution is 1:x:1-x:1, where x=0.3-0.
7.
4. The method for preparing the composite lithium iron manganese phosphate positive electrode material according to claim 1, characterized in that: The temperature of the hydrothermal reaction is 170-200°C; And / or, the hydrothermal reaction time is 5 to 8 hours.
5. The method for preparing the composite lithium iron manganese phosphate positive electrode material according to claim 1, characterized in that: The temperature of the secondary hydrothermal reaction is 150-170°C; And / or, the secondary hydrothermal reaction time is 2 to 5 hours.
6. The method for preparing the composite lithium iron manganese phosphate positive electrode material according to claim 1, characterized in that: The pore volume of the zinc MOF is 0.6 to 0.75 cm 3 / g; And / or, the BET specific surface area of the zinc MOF is 1300-1600m 2 / g; And / or, the D50 of the zinc MOF is 1-5 μm.
7. The method for preparing the composite lithium iron manganese phosphate positive electrode material according to claim 1, characterized in that: The mass ratio of lithium source in the precursor to zinc MOF is 100:8-20; And / or, the mass ratio of the zinc MOF to the sodium poly(p-styrene sulfonate) is 10:1-5.
8. The method for preparing the composite lithium iron manganese phosphate positive electrode material according to claim 1, characterized in that: After the secondary hydrothermal reaction, post-treatment is required, and the post-treatment includes the steps of filtering, washing and drying.
9. The composite lithium iron manganese phosphate positive electrode material prepared by the method for preparing the composite lithium iron manganese phosphate positive electrode material according to any one of claims 1 to 8.
10. The composite lithium iron manganese phosphate positive electrode material according to claim 9, characterized in that: The tap density of the composite manganese iron phosphate lithium positive electrode material is 0.8-1.2 g / cm 3 .
Citation Information
Cited By
Lithium manganese iron phosphate positive electrode material with consistent morphology, preparation method and positive electrode
CN121516840A